Investigate And Simulate DC/DC Buck Regulator By Using LTspice - Rashid, Mohd Sharimin (Universiti Sains Malaysia, 2018)
This paper presents an investigation and simulation of DC/DC buck converter by using LTspice. Buck converter is a converter that is capable of lowering input voltage as an output voltage. Pulse Width Modulation (PWM) signal with constant duty cycle to drive the switch of the converter. Instead of using the conventional buck converter, this project will replace the normal diode to Schottky’s diode and SMPS. The minimum size of inductor is calculated and the minimum value for the capacitor is calculated and simulated without affecting the circuit overall performance. The buck converter are made of several sub circuit such as comparator, voltage reference, SMPS and ramp voltage. Every sub-circuit are simulated separately and then as a whole. The author also present the simulation results and discussion (in Chapter 4) related to the theoretical aspects. Results shows that the DC/DC buck converter is able to maintain its load current at 1mA and load voltage of 1.32V at input voltage of 1.4V to 6V. The efficiency of the circuit according to the given limit of input voltage is more than 70%.